2003
DOI: 10.1021/es032402n
|View full text |Cite
|
Sign up to set email alerts
|

Peer Reviewed: Nonextractable Pesticide Residues in Soil

Abstract: How can we resolve conflicts in definition, regulatory requirements,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 37 publications
0
32
0
1
Order By: Relevance
“…Organics transferred to soil are retained by sorption to organic matter (Cousins et al, 1999), but incompletely subject to re-volatilisation due to the long-term dynamics of sorption ("aging"; e.g. Gevao et al, 2003;Lehnik-Habrink et al, 2010), a process that is hardly understood. PCBs undergo multiple deposition and (re-)volatilisation cycles on land and sea (Wania and Mackay, 1993;Klečka et al, 2000;Gouin and Wania, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Organics transferred to soil are retained by sorption to organic matter (Cousins et al, 1999), but incompletely subject to re-volatilisation due to the long-term dynamics of sorption ("aging"; e.g. Gevao et al, 2003;Lehnik-Habrink et al, 2010), a process that is hardly understood. PCBs undergo multiple deposition and (re-)volatilisation cycles on land and sea (Wania and Mackay, 1993;Klečka et al, 2000;Gouin and Wania, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As is known, bound residues are defined as parents or metabolites of contaminants left in sample after the sample was extracted by Soxhlet for 24 h [14,15,25]. Khan and Hamilton [33] demonstrated that a steady decrease of extractable prometryn was accompanied by a corresponding increase of bound residues.…”
Section: Predominance Of Solvothermal Processmentioning
confidence: 99%
“…This approach is a surface mediated process and adsorption of PCBs onto the surface plays an important role in the whole process [11]. But it is noteworthy that, a portion of PCBs was prone to be associated with soil organic matter such as humic acid (HA), bound humic acid (bound HA) [12,13] and thus result in the formation of unextractable (bound) PCBs [14,15]. Accordingly, these bound PCBs were difficult to be effectively disposed by capping approach [11,16].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, hazardous waste chemicals or microorganisms reach humans through several exposure routes, such as dermal contact with soil, ingestion of water and contaminated food, and inhalation. The degree of waste impacts is highly depended on their bioavailability [42] but not on the assumption of their total availability of extractable residues.…”
Section: Exposure Potentialmentioning
confidence: 99%